P-EGS23 Efficacy of Percutaneous Cholecystostomy and Timing of Tube Removal: An Observational Study from a busy District General Hospital. (16th December 2021) - Choh, Clarisa TP; Majkowska, Agata; Heugh, Claire; Cowie, Andrew S; Byrom, Richard; Bennett, David H; Davies, Nick A
Abstract: Background: Percutaneous cholecystostomy (PC) has traditionally been reserved for high-risk patients with cholecystitis who are unfit for surgical intervention, or as a temporizing measure for septic biliary patients to relieve sepsis and symptoms. However, there are currently no guidelines regarding the timing of tube removal following PC. The aim of this study is to evaluate the timing of tube removal following resolving inflammation and patency of biliary ducts, and its associated risks. Methods: Patient notes and imaging reports were retrospectively reviewed from those who underwent percutaneous cholecystostomy from January 2015-Dec 2020. Data collected included demographic details, symptom presentation, requirement of ITU admissions, details of cholecystostomy, post-operative complications from the tube, outcomes following PC, and mortality rates within 30 days of the procedure. Patients were graded by their severity of their cholecystitis according to the 2018 Tokyo Guidelines, and these were correlated with morbidity and mortality outcomes within 1 year of the procedure. Results: There were 55 females and 65 males, with a mean age of 75.2 years (range 45-96 years). Approximately 45% of patients were diabetic and had comorbidities. On presentation, 54% (65/120) patients had elevated inflammatory markers (WCC/CRP), and 20% of patients had associated deranged liver function tests. Majority of patients had moderate or severe acute cholecystitis, with over 25% (31/120) of patients presenting with sepsis, and 6 required admission to intensive care. The median time from diagnosis of acute cholecystitis to percutaneous cholecystostomy was 8.5 days (range 1-64 days). Tube removal was performed after a median time of 31 days (range 1-142 days). Morbidity rate was observed to be 8-10%, comprising of complications such as tube displacement, leakage around the drain, bleeding and liver abscesses. Only 18.3% (22/120) of patients were deemed to be fit for further surgical intervention, of which 13 of those underwent a cholecystectomy thereafter. Unsurprisingly, 38% of these patients had recurrent biliary symptoms, and a 30% mortality rate.   Conclusions: Percutaneous cholecystostomy is a safe option in high-risk surgical patients for symptom relief, and is a crucial step in temporizing and de-escalating sepsis. However, this study suggests that timing of cholecystostomy removal is variable, and is associated with high morbidity. Consideration needs to be given to shorten the time to tube removal, to minimise risks, if certain criteria are met to ensure safety and efficacy.